New non-linear color look-up table for visualization of brain fractional anisotropy based on normative measurements - principals and first clinical use - Keller, Jiří; Rulseh, Aaron M; Komárek, Arnošt; Latnerová, Iva; Rusina, Robert; Brožová, Hana; Vymazal, Josef (PloS one, 2013)
Fractional anisotropy (FA) is the most commonly used quantitative measure of diffusion in the brain. Changes in FA have been reported in many neurological disorders, but the implementation of diffusion tensor imaging (DTI) in daily clinical practice remains challenging. We propose a novel color look-up table (LUT) based on normative data as a tool for screening FA changes. FA was calculated for 76 healthy volunteers using 12 motion-probing gradient directions (MPG), a subset of 59 subjects was additionally scanned using 30 MPG. Population means and 95% prediction intervals for FA in the corpus callosum, frontal gray matter, thalamus and basal ganglia were used to create the LUT. Unique colors were assigned to inflection points with continuous ramps between them. Clinical use was demonstrated on 17 multiple system atrophy (MSA) patients compared to 13 patients with Parkinson disease (PD) and 17 healthy subjects. Four blinded radiologists classified subjects as MSA/non-MSA. Using only the LUT, high sensitivity (80%) and specificity (84%) were achieved in differentiating MSA subjects from PD subjects and controls. The LUTs generated from 12 and 30 MPG were comparable and accentuate FA abnormalities.
Keywords: Multiple System Atrophy; thalamus; lidé; mladiství; software; Adult; Anisotropy; Brain Mapping; Middle Aged; Parkinson Disease; Parkinsonova nemoc; Frontal Lobe; multisystémová atrofie; Diffusion Tensor Imaging; bazální ganglia; barva; corpus callosum; senzitivita a specificita; Female; Basal Ganglia; Sensitivity and Specificity; Healthy Volunteers; Thalamus; Reference Values; Adolescent; Humans; zobrazování difuzních tenzorů; algoritmy; Software; čelní lalok; lidé středního věku; Algorithms; Signal-To-Noise Ratio; poměr signál - šum; mužské pohlaví; mladý dospělý; anizotropie; ženské pohlaví; Color; Corpus Callosum; Young Adult; mapování mozku; Aged, 80 and over; senioři nad 80 let; Male; mozek; Aged; Brain; referenční hodnoty; dospělí; zdraví dobrovolníci pro lékařské studie; senioři